Salmonella Typhi sense host neuroendocrine stress hormones and release the toxin haemolysin e - Karavolos, M; Bulmer, D; Spencer, H; Rampioni, G; Schmalen, I; Baker, S; Pickard, D; Gray, J; Fookes, M; Winzer, K; Ivens, A; Dougan, G; et al. (2011)
Salmonella enterica serovar Typhi (S. typhi) causes typhoid fever. We show that exposure of S. typhi to neuroendocrine stress hormones results in haemolysis, which is associated with the release of haemolysin E in membrane vesicles. This effect is attributed to increased expression of the small RNA micA and RNA chaperone Hfq, with concomitant downregulation of outer membrane protein A. Deletion of micA or the two-component signal-transduction system, CpxAR, abolishes the phenotype. The hormone response is inhibited by the β 2-blocker propranolol. We provide mechanistic insights into the basis of neuroendocrine hormone-mediated haemolysis by S. typhi, increasing our understanding of inter-kingdom signalling. © 2011 European Molecular Biology Organization Embo.